Microwave-assisted synthesis of Mg:PbI2 nanostructures and their structural, morphological, optical, dielectric and electrical properties for optoelectronic technology*Project supported by the Deanship of Scientific Research at King Khalid University (Grant No. R.G.P1/207/41), the Deanship of Scientific Research at Princess Nourah bint Abdulrahman University through the Fast-track Research Funding Program, and Deanship of Research, University of Hail. (October 2020) - Shkir, Mohd.; Khan, Ziaul Raza; Alshahrani, T; Chandekar, Kamlesh V.; Manthrammel, M Aslam; Kumar, Ashwani; AlFaify, S
Abstract : This work reports the cost-effective growth of Mg:PbI2 nanostructures with 0, 1, 2.5 and 5.0 wt.% Mg doping concentrations. Structural, vibrational, morphological properties are analyzed using x-ray diffraction (XRD), Raman spectroscopy and scanning electron microscopy (SEM). XRD and Raman studies confirm the monophasic hexagonal system of Mg:PbI2, and no additional impurity peaks are detected. The Scherrer formula is used to determine sizes of crystallites to be in the range of 47–52 nm. EDX/SEM e-mapping analyses confirm the incorporation of Mg in PbI2 matrix and its uniform distribution throughout the sample. The hexagonal nanosheet- and nanoplate-like morphologies are detected in SEM images for pure and Mg-doped PbI2 . An optical band gap of nanostructures is obtained from Tauc's relation to be in the range 3.0–3.25 eV. Dielectric and electrical properties are found in significant enhancement as Mg doping in PbI2 matrix, also the conduction mechanism is discussed.